Modeling changes in the global carbon cycle-climate system - Steinacher, Marco (2011)
There is strong evidence that human activities are altering the Earth’s climate and biogeochemical cycles. Anthropogenic carbon emissions have increased the concentration of carbon dioxide (CO2) in the atmosphere by about 40% since preindustrial times. The elevated CO2 levels are the main drivers of changes in the atmosphere’s radiative balance as well as in the ocean’s chemistry. This thesis investigates consequences of the anthropogenic interference with the coupled carbon cycle-climate system. A main focus is on the acidification of the oceans caused by the uptake of anthropogenic CO2. Further, interactions between climate and the carbon cycle are addressed. Numerical simulations with coupled carbon cycle-climate models are used to quantify future changes under several scenarios of CO2 emissions, land-use change, and other forcings. Such projections are important for assessing potential impacts on ecological and socio-economic systems. Moreover, they provide a basis for developing mitigation and adaptation strategies and contribute to the understanding of the complex carbon cycle-climate system in general. The introduction in chapter 1 provides an overview of the global carbon cycle with an emphasis on ocean biogeochemistry. Further, important concepts such as radiative forcing, feedbacks, and climate sensitivity are introduced. The influence of human activities, predominantly the emissions of CO2, is summarized and discussed with respect to ocean acidification and the perturbation of the radiative balance, followed by an overview of the associated changes in climate and feedbacks within the coupled carbon cycle-climate system. Chapter 2 consists of three publications presenting projections of ocean acidification with a special focus on the Arctic Ocean. The global coupled carbon cycle-climate model NCAR CSM1.4-carbon is applied to simulate ocean acidification for the industrial period and for the two IPCC SRES emission scenarios A2 and B1 (2000–2100). The results support the important finding of earlier ...